Case report of IgG4-related appendiceal disease: A challenging disease - Dias, Adriano Basso (Medicine (Baltimore), 2020)
RATIONALE: Immunoglobulin G4 (IgG4)-related disease is an increasingly recognized immune-mediated entity that can affect virtually every organ system. Depending on the location of the disease, it can present a wide range of clinical manifestations and even mimic malignancies. Appendiceal involvement in patients with IgG4-related disease is particularly rare and very few cases are reported in the literature. PATIENT CONCERNS: We report a case of IgG4-related appendiceal disease in a 42-year-old woman who presents with a subacute onset of right lower quadrant abdominal pain. DIAGNOSIS: Abdominal computed tomography showed a markedly enlarged appendix, raising the concern of malignancy. The diagnosis of IgG4 appendiceal disease was confirmed by postoperative histopathologic and immunohistochemical examination. INTERVENTIONS: The patient underwent right hemicolectomy. OUTCOMES: After the surgery, the patient had an uneventful recovery and reported a resolution of her symptoms. The serum IgG4 was revaluated 5 days after surgery and returned to its normal values. At the 3-year follow up, the patient had no recurrence of symptoms and her imaging exams remain unremarkable. LESSONS: This study reports the fifth case of IgG4-related appendiceal disease. Increasing awareness of this condition may influence the management of these patients, once patients with IgG4-related disease should be monitored after treatment, due to the risk of recurrence or involvement of other organs.